Islamic Republic of Mauritania : Sixth Review Under the Extended Credit Facility Arrangement and Request for Waiver of Nonobservance of a Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for the Islamic Republic of Mauritania. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2021)
The COVID-19 pandemic is having a severe human, economic, and social impact on Mauritania. The economy is estimated to have contracted by about 2 percent in 2020 and the crisis generated large financing needs. The authorities responded swiftly to mitigate the impact of the pandemic while international partners provided grants, loans, and debt service suspension. This, compounded by higher commodity exports (iron ore and gold) and some delays in emergency spending, resulted in unexpected fiscal surpluses and an accumulation of international reserves, which may now be used to support the recovery in 2021-22. The outlook remains highly uncertain and dependent on volatile commodity markets, with sizable downside risks in case new waves of the pandemic spill over into Mauritania.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet